Candomblé rituals and food practices in Italy and Brazil: an ethnographic comparison (Antropolítica - Revista Contemporânea de Antropologia, 2020)
This paper focuses on the relationship between food practices, preparation of Candomblé ritual offerings and performance of rituals in a transnational case study. My interest here is to consider two ethnographic accounts of Candomblé rituals in Italy and Brazil. I will analyze how Italian practitioners perceive different aspects of the preparation of ritual offerings and what values are at stake in the cooking and consumption of food and food offerings. I will show how memory and the senses are essential to build a new idea of familiarity and to learn new skills within the ritual practice.